ChemInform Abstract: Catalyst Design with Atomic Layer Deposition. Issue 18 (May 2015) - O'Neill, Brandon J.; Jackson, David H. K.; Lee, Jechan; Canlas, Christian; Stair, Peter C.; Marshall, Christopher L.; Elam, Jeffrey W.; Kuech, Thomas F.; Dumesic, James A.; Huber, George W.
Abstract Review: 247 refs.